Design and Development of a Non-Verbal Documentary Video on the Ten Years of Joko Widodo’s Administration (A Practice-Led Study Using YouTube Analytics) - Ma’mur, Angghi Muliya; Kurniawan, Fajar; Yuniani, Hani; Cindrakasih , RR. Rosita (Sean Institute, 2025)
This study presents the design and development of a non-verbal documentary video that visually narrates the decade of Joko Widodo’s administration in Indonesia. Using a practice-led approach, the research focuses on crafting a ten-minute documentary that emphasizes visual storytelling through natural sounds, ambient audio, emotive music, and readable subtitles to enhance accessibility and engagement. The production process involved three key stages: pre-production, production, and post-production, each emphasizing the aesthetic and communicative aspects of visual narrative. Evaluation was conducted using YouTube engagement indicators to assess viewer responses and interaction patterns. The findings reveal that the integration of human-interest visuals, contextual sound design, and data-driven graphics strengthens audience immersion and message retention. This study contributes to the field of visual communication design by offering practical insights into how non-verbal storytelling can effectively convey development narratives within limited duration and digital distribution platforms.